Peranan Audit Manajemen Dalam Rangka Pengendalian Efisiensi dan Efektivitas Fungsi Keuangan di PT Bank Mandiri ( Persero) - Alisa Afrianti; Tuti Meutia (Jurnal Riset Akuntansi, 2024)
This study explores the role of Management Audit in controlling the Efficiency and Effectiveness of the Financial Function at PT Bank Mandiri (Persero). Management audit plays an important role in evaluating the performance of management and internal control systems in an organization. By conducting periodic management audits, PT Bank Mandiri can identify potential problems, weaknesses, and opportunities for improvement in financial management so as to improve performance and reduce potential risks. The findings suggest that Management Audit is not only important to ensure compliance with internal regulations and policies but also to optimize resource utilization, identify profitable investment opportunities, and minimize financial risks. This serves as a strategic instrument in supporting the achievement of company goals and maintaining overall business continuity.This paper delves deeper into the importance of Management Audit in maintaining the financial health and business continuity of PT Bank Mandiri in the midst of the evolving dynamics of the banking industry. The analysis conducted, among others, examines management audit practices implemented by banks, challenges faced, and recommendations for improving the effectiveness of management audits to support the achievement of optimal financial and operational goals at PT Bank Mandiri.